Symbolic Language Interpretation of Cultural Heritage Preservation Policy of Surabaya City - Lunariana Lubis; Bintoro Wardiyanto; Erna Setijaningrum (Pusjar SKPP Lembaga Administrasi Negara, 2025)
This study explores the symbolic use of language in Surabaya's cultural heritage preservation policies using the Interpretive Policy Analysis (IPA) approach. It analyzes policy documents and interviews with stakeholders and communities related to Hotel Majapahit, Tugu Pahlawan, and Tanjung Perak Main Harbormaster Building. The findings highlight how language in policy is not merely communicative but symbolic, reflecting community values, beliefs, and emotional ties to heritage. The paradigm shift in policy, from conservative to progressive and localistic approaches, is reflected in the change from